DISTRIBUTION OF FEBRILE NEUTROPENIA INCIDENCE IN LEUKEMIA PATIENTS UNDERGOING CHEMOTHERAPY - Rudi, Rudi; Ismawati, Rini; Ayu Puspitarini, Diah; Umar, Nadia; Indriyani, Cunani; Rahmayani, Fitri; Megawati Sinaga, Laura; Purwanti, Retno (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
One of the serious complications that often occurs in leukemia patients undergoing chemotherapy is febrile neutropenia, especially in isolation rooms with weak immune systems. The purpose of this study was to provide an overview of the prevalence of febrile neutropenia and the characteristics of leukemia patients undergoing chemotherapy in the Decreased Immunity Isolation Room at Dharmais Cancer Hospital in Jakarta. Data, collected through a descriptive retrospective study design, were obtained from medical records of patients receiving chemotherapy for leukemia between 2013 and 2014, with a sample size of 71 patients calculated using the Slovin formula. The variables analyzed included gender, age, diagnosis, type of chemotherapy, absolute neutrophil count value, and the incidence and characteristics of febrile neutropenia. The results showed that 83.1% of the total patients experienced febrile neutropenia, with the most frequent occurrence on days 8 to 20 after chemotherapy. Most patients with febrile neutropenia had an absolute neutrophil count value of less than 500 cells/µL, indicating a high risk of infection. The majority of patients received antibiotics for the management of febrile neutropenia, with the most commonly used antibiotics being Meropenem and Ceftazidime. This study can help healthcare providers prevent and manage febrile neutropenia in leukemia patients and provide a basis for further research to develop better interventions.